Supramolecular subphthalocyanine complexes–cellular uptake and phototoxicity. Issue 55 (10th June 2020) - Dubbert, Justin; Höing, Alexander; Riek, Nathalie; Knauer, Shirley K.; Voskuhl, Jens
Abstract : In this contribution a supramolecular approach was described using subphthalocyanines as guests for cyclodextrins and cyclodextrin polymers. The complexes were investigated concerning their phototoxicity as well as the cellular uptake for bio-imaging. Abstract : In this communication we report on the synthesis and application of axially functionalized boron-subphthalocyanines (SubPC) which are able to form host–guest complexes with cyclodextrins. Here, a tert -butylphenyl substituted SubPC was investigated concerning its complexation with β-cyclodextrin (β-CD) and a β-cyclodextrin polymer. NMR-titrations showed the formation of a 1 : 1 complex with β-CD. These assemblies were analyzed for their cellular distribution as well as their phototoxicity towards HeLa cells.